Global Profit Shifting of Multinational Companies: Evidence from CbCR Micro Data - Clemens Fuest; Stefan Greil; Felix Hugger; Florian Neumeier (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper uses micro data from country-by-country reporting of more than 3600 large multinational companies operating in 238 jurisdictions to analyze global profit shifting to avoid taxes. These companies report 7% of their global profits in jurisdictions with effective average tax rates below 5%, but only 0.4% of their employees and 3% of their tangible assets are located there. We find that globally, these companies reduce their tax burden by EUR 53 billion (15% of their overall tax payments) by shifting profits to low-tax countries. Losses of the US and Canada are slightly lower, the losses of the EU 27 member states are similar to the global average. 60% of the profit shifting is carried out by the 10% largest multinational companies. We show that taking into account non-linearities in profit shifting and subsidiaries reporting zero profits is of key importance for accurate estimates of profit shifting. We also investigate profit shifting channels and provide evidence suggesting that the location of IP and equity in low tax countries as well as the provision of loans to entities in high tax countries play a key role for tax planning.
Keywords: F23; H25; H26; 330; : corporate taxation; tax avoidance; profit shifting; multinational enterprises; country-by-country reporting